PENERIMAAN MASYARAKAT KUALA TERENGGANU TERHADAP AR-RAHNU KETIKA KRISIS KEWANGAN PASCA PANDEMIK COVID-19: SATU KERANGKA KONSEPTUAL - Yahaya, Salimah; Hassan, Surita Hartini Mat; Abdullah, Sakinatul Raadiyah; Hamid, Che Khadijah; Mohd Noor, Nor Adila (Jurnal 'Ulwan, 2024)
A few communities are affected by the Movement Control Order (MCO) implemented by the government. Some lost their sources of income and jobs. Throughout the implementation of the MCO, the scenario of our society is explicit when encountering the financial crisis as some of them queued up in front of the pawnshop premises to get loans. This scenario seems to give the impression that pawning has become a good solution to their temporary financial crisis. This is because pawnbrokers are able to provide short-term cash loans immediately. There are two types of pawnshops operating in Terengganu, namely conventional pawnshops (non-Sharia compliant) and Islamic or Ar-Rahnu pawnshops (Sharia compliant). The question is, how does the community in Kuala Terengganu district accept Ar-Rahnu? Thus, this study was conducted to identify and analyze the factors that influence the acceptance of the community in Kuala Terengganu towards Ar-Rahnu. This study was in the preliminary stages; to answer the question raised, a qualitative study was conducted by reviewing relevant previous studies. Subsequently, a conceptual framework was formed based on the review. Data of this study were collected from documentation and literature review, and were subjected to content analysis method. The findings of this study revealed that the community in Kuala Terengganu are more likely to choose Ar-Rahnu as a profitable temporary financial solution as this financing approach is simpler and more transparent compared to conventional approach. The conceptual framework developed could be regarded as a benchmark for future studies.